Интернет Вещей в структуре умного предприятия - Гриценко, В.И.; Тимашова, Л.А. (Управляющие системы и машины, 2017)
Рассмотрены вопросы, связанные с применением технологий Интернета Вещей на промышленных предприятиях, основы их использования, примеры эффективности реализации и определяющая роль платформы Интернета Вещей. Именно она обеспечивает сбор и анализ данных, что является ключевым моментом в современной автоматизации промышленной сферы. Раскрыты особенности зарождения и развития концепции «Интернет Вещей» на современном этапе становления инновационной экономики в Украине и мире. Розглянуто питання, пов'язані з застосуванням технологій Інтернету Речей на промислових підприємствах, підстави їх використання, приклади ефективності реалізації та визначальна роль платформи Інтернету Речей. Саме вона забезпечує збір та аналіз даних, що є ключовим моментом у сучасній автоматизації промисловій сфери. Розкрито особливості зародження і розвитку концепції «Інтернет Речей» на сучасному етапі становлення інноваційної економіки в Україні та світі. Introduction. The creation of completely automated system of the operation monitoring of the devices and people in real time is one of the most perspective direction of the clever enterprises development. Its major characteristics are a mobility, a possibility of access to the necessary information at any time, in any place and from any devices. Purpose. Problems and technologies of the Internet of Things (IoT) use are considered, as the stage of the long and not ended yet revolution in the field of computing systems and the means of communication. The Internet of Things is a term that defines all the expanding complex of the intelligent devices connected to each other. Methods. The technological component when built-in devices are the «Things» in the Internet is worked out, their distinctive features are: data collection with low recurrence and the small volume of the used data. These devices exchange data with each other and provide data via user interfaces. Some built-in devices from the Internet of Things require a broadband streaming. But most of them require transmission of data packets only from time to time. The same as people receive the new methods of access to the world by means of smartphones, Internet of Things will create a new paradigm providing the continuous access to necessary information. Results. The Internet of Things concept, its origin and development features at the present stage of the innovative economy formation in Ukraine and the world are listed. Conclusion. The Internet of Things technology is an important direction of a large interindustry technical problem – the intellectualization. The effect of this direction will increase in process of the development of the models, figurative thinking and intellectual management allowing in the conditions of incomplete information making the balanced and weighed decisions. It is important to develop the perspective means of information processing, which along with calculations, are capable to implement the difficult models of the artificial thinking.